Performance Model of Nurse Community Approach to Organizational Culture in Indonesia - Suhartono Suhartono; Sulistiawati Sulistiawati; Esty Yunitasari (Intelektual Pustaka Media Utama, 2016)
National problem faced by Indonesia today is the handling of the low quality of Human Resources (HR). HR issues that need attention is the issue of performance. Performance is the rate of success in carrying out the task, as well as the ability to achieve the goals set. The aim of this study was to determine the influence of individual factors, organizational factors, organizational and cultural factors on the Performance of Nurses. This study used a cross sectional study approach. The population used in this study were nurses ponkesdes Tuban and Lamongan district in accordance with the inclusion criteria as much as 55, with a sample size of 48 respondents specified research using simple random sampling technique. The independent variable in this study is the individual factors (abilities and skills), organizational cultural factors and organizational factors, dependent variable is the performance of nurse ponkesdes. Instruments used in the collection of data in the form of questionnaires and performance evaluation sheet. Research analysis using simple linear regression test. Simple linear regression analysis showed variable organizational cultural factors were not statistically significant effect on the performance of the p-value (0.000), organizational factors also significantly influence the performance of the pvalue (0.027). While the variable factors of individual (skills and abilities) does not significantly influence the performance of the p-value (0.103).